2019
DOI: 10.1155/2019/3860142
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Ossification: A Challenging Complication of Total Hip Arthroplasty: Risk Factors, Diagnosis, Prophylaxis, and Treatment

Abstract: Background. This review is intended to summarize the risk factors, classification, diagnosis, and treatment of heterotopic ossification (HO) of previously published studies. Results. Heterotopic ossification is a common complication of total hip arthroplasty. Its prevalence is not the same in all of the patient groups. Frequency of HO varies from 15 to 90%. Hip ankylosis, male gender, and previous history of HO are said to be risk factors with a significant level. Diagnosis is based on a single AP radiograph: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 58 publications
2
65
0
2
Order By: Relevance
“…The observed incidence of HO in the institutional cohort was 52%, similar to previous published research [ 28 , 29 ]. It is unclear how the surgical approach can affect HO incidence, and there are no unequivocal opinions concerning the best procedure to prevent HO in terms of radiation therapy (single 7–8 Gy dose) [ 36 , 37 ] or chemoprophylaxis (including indomethacin, diclofenac or ibuprofen) [ 38 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observed incidence of HO in the institutional cohort was 52%, similar to previous published research [ 28 , 29 ]. It is unclear how the surgical approach can affect HO incidence, and there are no unequivocal opinions concerning the best procedure to prevent HO in terms of radiation therapy (single 7–8 Gy dose) [ 36 , 37 ] or chemoprophylaxis (including indomethacin, diclofenac or ibuprofen) [ 38 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is evidence, supported by our results, that diclofenac supports in vitro osteogenic differentiation but the mechanism remains unknown. It is known, that BM-MSCs have compensatory mechanism to restore PEG2 synthesis as an intrinsic regulation of osteogenic differentiation if these cells are treated with NSAIDs [ 26 ] while the inhibition of the prostaglandin synthesis in vivo result is a limitation of pathologic bone growth, which makes these drugs very popular to avoid heterotopic ossifications after total hip replacement [ 10 , 11 ]. However, recent systematic reviews confirmed the absence of robust in vitro or clinical data regarding NSAIDs and their impact on bone formation, and encouraged researchers to perform further basic science and clinical studies to clarify the risks and benefits of NSAIDs in patients with musculoskeletal disorders [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory potential of these drugs reduces symptoms caused by the inflammatory component in pathologies like activated arthrosis and post-surgical inflammatory response [ 7 ]. An additional feature of NSAIDs (e.g., diclofenac and ibuprofen) is their ability to reduce heterotopic ossifications after total hip arthroplasty and acetabular fracture treatment [ 8 , 9 , 10 , 11 , 12 ]. Non-selective NSAIDs inhibit COX-1 and COX-2, while selective NSAIDs only inhibit COX-2.…”
Section: Introductionmentioning
confidence: 99%
“…Single fraction RT of 7 Gy postoperatively and indomethacin were the two most common used regimens with equal effectiveness. 38 Finally, three meta-analysis of randomizes clinical trials (RCTs) have compared RT to other treatment options mainly NSAIDs. In the two meta-analysis from Vanken et al , there was not any statistically significant difference, although Grade 3 and 4 HO was less often seen after radiation therapy while NSAIDs were considerably more cost effective as a treatment modality.…”
Section: Discussionmentioning
confidence: 99%